HUBUNGAN ANTARA ARTIKEL MENGENAI GAME DAN TEKNOLOGI INFORMASI PADA SCOPUS: STUDI BIBLIOGRAFI - Yaka Bagus Pratama; Akhmad Kusuma Wardhana; Prasetyo Adi Nugroho (Perpustakaan Nasional RI, 2020)
Game as a media currently it has been implemented in several fields, including education. The implementation of games in education is said to be able to offer innovative and effective learning methods. In this new era, game is closely related with information science.this study aims to observe the connection between game and information science through the articles which are indexed by Scopus. This study is qualitative using blibliography method in collecting the data. The subjects are articles in Scopus website that contains the keywrods “ game” and “information sceince”. The data was analyzed using VosViewer to reveal the conncetion between tow of them. The result shows that between tow subject there are more breaoder result that are divided into several sub-subject. Some parts of subject have connection with information that becomes bridges shows clear relationship about the trends of science subjects, includes game subjects in the information science family. It can concluded that there was a citation relationship and trends in writing scientific articles about games that were linked to information science.